Trade and welfare effects of a potential free trade agreement between Japan and the United States - Timo Walter (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
This paper deals with the trade and welfare effects of a potential bilateral trade agreement between the US and Japan. A possible agreement is currently being discussed between Washington and Tokyo, although, there is also the alternative for the US government joining Trans-Pacific Partnership (TPP). Based on the theoretical model of Caliendo and Parro (2015) I analyse the welfare gains of such a bilateral free trade agreement (FTA) in the style of Aichele et al. (2014). In particular, I simulate three scenarios with different levels of integration: The reduction of tariffs only, the scenario of a shallow FTA, and a deep FTA. In addition, the paper compares the trade and welfare changes of a deep FTA to the welfare effects of TPP. The findings are that Japan has the highest welfare gains with a FTA (0.085%), whilst the United States benefits the most from TPP with a welfare gain of 0.05%.
urn:nbn:de:bsz:100-opus-15045
Keywords: F13; F14; F17; 330; Trade agreements; Gravity model; Counterfactual equilibrium; Intermediate goods; Input-output linkages; Japan; United States